Cross-bite treatment with functional orthopedic maxillary Bimler C. Case report - Bedoya, Antonio; Gallego, Mónica (Revista Estomatología, 2011)
Managing a crossbite unidental in an adolescent by means of functional orthopedic treatment maxillary (Bimler C) after a few months of permanent use, it is unsatisfactory in the functional, occlusal and aesthetic area. Allowing for the patient with a point pleasant, and avoiding a sequence of tissue damage dental, bone and periodontal that can have irreversible consequences for teens. It is necessary to a good clinical examination and a sound plan of treatment for the functional orthopedics of the Maxillas allow for the correct solution to this malocclusion. Key words: Anterior crossbite, orthopedic treatment maxillary, Bimler C.